Kewajiban Menanam Pohon sebagai Syarat Pernikahan Perspektif Hukum Perkawinan Islam dan Teori Tujuan Hukum Gustav Radbruch - Ulil Bahrul Fadli; Lukman Santoso (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Humans need the environment, just as the environment needs humans. This shows that humans and the environment influence each other. The implementation of the Magetan Regent's regulation on the Mandatory Tree Planting Movement provides broad benefits, such as fostering a sense of shared responsibility and creating job opportunities. On the other hand, in its implementation, the location for planting trees and the size of the trees are not specified. This creates uncertainty that impacts the legal certainty created by the regulation. The research method used in this study is a qualitative descriptive research method with field research and a normative approach. The research questions in this study are (1) What are the implications of Magetan Regent Regulation No. 11 of 2020 concerning the Mandatory Tree Planting Movement on marriage from the perspective of Gustav Radbruch's Theory of Legal Purpose in Bibis Village, Sukomoro District, Magetan Regency? (2) How is the implementation of the obligation to plant trees as a condition for marriage according to Gustav Radbruch's Theory of Legal Purpose in Sukomoro District, Magetan Regency? Although it is not listed in the valid and harmonious requirements for marriage, it does not deviate from or violate any norms in any aspect. The implementation of public policy has been carried out well, starting from good communication and adequate resources.